PREDICTING THE SEVERITY OF BRONCHIOLITIS IN A RESOURCE-POOR SETTING - Anil Drolia; Pooja Dewan; Piyush Gupta (Amaltea Medical Publishing House, 2010)
Introduction: Bronchiolitis is the leading acute viral infection in infants. Early diagnosis and determination of severity of bronchiolitis in children is crucial for rapid initiation of treatment. This may be diffi cult to achieve in a resource-poor setting, where laboratory support and facilities for hospitalization are limited. Objectives: To determine the clinical predictors for severe bronchiolitis in children below 24 months of age in a resource-poor setting. Place and duration of study: Paediatric emergency department of a tertiary hospital over a period of one year. Patients and Methods: Children below 24 months age presenting with bronchiolitis. Children were classifi ed as having severe or moderate bronchiolitis, depending upon the improvement seen in respiratory rate 48-72 hours after admission. Nasopharyngeal aspirates and serum samples obtained from the cases were used to detect the viral etiology. The clinical characteristics in the two groups were compared using Chi square/ student's t-test where applicable, and were correlated with the disease severity. The sensitivity, specifi city, and relative risk for the various clinical parameters in detecting severity of bronchiolitis were obtained by statistical analysis. Results: Bronchiolitis accounted for 1.7% of the pediatric admissions. Respiratory rate ≥ 68/m, and the use of accessory muscles of respiration were found to be major clinical determinants for severe bronchiolitis. Infl uenza virus (H3N2) followed by respiratory syncytial virus were the dominant viral pathogens. Conclusion: Respiratory rate and the use of accessory muscles of respiration can predict the severity of bronchiolitis in the absence of advanced diagnostic facilities in developing countries.